Individualized goal attainment scaling during a trial of positive behaviour support in adults with acquired brain injury. Issue 9 (21st October 2022) - Gould, Kate Rachel; Feeney, Tim J.; Hicks, Amelia J.; Ponsford, Jennie Louise
ABSTRACT: Background: Challenging behaviours after acquired brain injury (ABI) cause distress and reduce community participation. Evidence-based and effective interventions are needed. Positive Behaviour Support (PBS) interventions, such as PBS + PLUS, are person-driven and context-sensitive approaches which aim to improve quality of life and enhance behavioural self-regulation. This study aimed to expand the empirical outcomes of a recent waitlist-controlled trial of PBS + PLUS by examining individualized goal attainment. Method: Participants were 44 adults with severe ABI sustained on average nine years previously (Range = 0.6–26) from the combined trial cohort who completed the intervention. Using Goal Attainment Scaling, trial therapists developed and reviewed goals collaboratively with the person with ABI and their natural supports. Results: The 182 goals in the sample focussed on psychological wellbeing, interpersonal relationships, routines and self-care. By the end of 12-month intervention, 84.6% of goals were achieved and 53.3% exceeded their expected outcome. Conclusions: These findings indicate high levels of personally meaningful outcomes in a broad range of life-domains can be obtained for participants with severe ABI using PBS + PLUS. Whilst these results should be considered in combination with the findings of the waitlist-controlled trial, they contribute to the growing literature regarding benefits of PBS in enhancing quality of life post-ABI. Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12616001704482.